RELEVANSI FILSAFAT ILMU TERHADAP PEMBENTUKAN KARAKTER - Ryan Nurmansyah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Philosophy of science is a branch of philosophy that focuses on scientific ideas and concepts. The process of developing one's attitudes and values is known as character building. The way the philosophy of science influences one's world view and perception of the nature of truth shows the relationship between philosophy of science and character building. Several characters such as openness, logic, discipline, and morality can be grown through the study of philosophy of science. Philosophy of science can also assist one in understanding the value of practicing critical and rational thinking when making judgments as well as the fact that knowledge and truth are constantly developing and increasing. As a result, having an understanding of the philosophy of science is felt to be very important in helping each individual in their life.